1995
DOI: 10.1093/jmedent/32.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Differentiation and Diagnostic Loci of Anopheles nuneztovari, An. trinkae, and An. rangeli (Diptera: Culicidae)

Abstract: Samples of Anopheles rangeli Gabaldon, Cova Garcia & Lopez, An. trinkae Causey, and An. nuneztovari Gabaldon from Venezuela, Ecuador, Brazil, and Bolivia were analyzed for genetic variability at 24 enzyme loci. Estimates of genetic variability for An. rangeli and An. trinkae from Ecuador and for An. nuneztovari in Venezuela had the following ranges: 46-58% polymorphic loci, 1.7-2.0 (SEM = 0.1-0.3) mean number of alleles per locus, and 0.069-0.113 (SEM = 0.03-0.04) expected mean heterozygosity. Genetic variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
23
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 0 publications
7
23
1
Order By: Relevance
“…Studies involving characters (morphological, genetic or biochemical) between species of Anopheles are sometimes ambiguous because of the limited distributions of some species. Consequently, these characters may become uninformative when applied to the entire geographic distribution of a taxon (Fritz et al 1991;Fritz et al 1995). In addition, chromosomal inversions and molecular markers are not always congruent for interspecific discrimination within the Anopheles genus (Dusfour et al 2004).…”
Section: Pcr-rapd and Pcr-rflp Polymorphisms Detected In Anopheles Crmentioning
confidence: 99%
“…Studies involving characters (morphological, genetic or biochemical) between species of Anopheles are sometimes ambiguous because of the limited distributions of some species. Consequently, these characters may become uninformative when applied to the entire geographic distribution of a taxon (Fritz et al 1991;Fritz et al 1995). In addition, chromosomal inversions and molecular markers are not always congruent for interspecific discrimination within the Anopheles genus (Dusfour et al 2004).…”
Section: Pcr-rapd and Pcr-rflp Polymorphisms Detected In Anopheles Crmentioning
confidence: 99%
“…Cytotype A occurs throughout the Amazon Basin, cytotype B is observed in populations from western Venezuela (eastern Andes) and Genetic divergence in mitochondrial DNA of Anopheles nuneztovari (Diptera: Culicidae) from Brazil and Colombia cytotype C is found in Colombia and western Venezuela (western Andes). Comparative isozyme studies have shown low differentiation between populations from Brokopondo (Suriname) and Barinas (Venezuela) (Steiner et al, 1980), as well as between populations from both sides of the Andes, in Venezuela (B and C cytotypes) (Fritz et al, 1995). Other investigations have suggested that populations from the Brazilian Amazon are genetically similar.…”
Section: Introductionmentioning
confidence: 99%
“…9 Studies on behavior, polytene chromosomes, isozymes, male genitalia, eggs, sequences of nuclear genes, and mitochondrial (mt) DNA of geographic populations of A. nuneztovari have shown different degrees of conspecific divergence or even evidence for a species complex. [10][11][12][13][14][15][16][17][18][19][20] Elliott suggested two allopatric forms or ecotypes for this species based on behavioral differences. 10 Populations from western Venezuela and northern Colombia described as human malaria vectors were mainly anthropophilic and endophagic, with a biting peak around midnight.…”
mentioning
confidence: 99%